Constructing from discord the word and the nation in My Sad Republic - Santos, Jaimee Faith J. (2014)
As a first place winner of the Centennial Literary Prize, Eric Gamalinda’s My Sad Republic (2000) is inextricably tied to discourses about the nation and its formation. In particular, it demonstrates the mutually constitutive relationship between the nation and the novel. My Sad Republic’s participation in the political project of nation-building is revealed not only in its entry and subsequent success in a large-scale government-sponsored contest, but also in its documentation of the components of nation-formation. Furthermore, the novel mimics the heterogeneous composition of the nation through its combination of historical, marvelous and romantic elements, as well as through the multiplicity of voices that its characters represent. Paradoxically, however, the novel also shows how the very diversity of individuals that constitute the nation inevitably leads to violent conflicts that hinder the actualization of the nation. The novel hence encourages the idea of self-sacrifice, the surrender of various personal agenda for the sake of a single national interest. At the same time, it also shows how the inherently problematic construction of the nation can be imagined only through literature, specifically the novel. The nation, in other words, depends on the novel not only for the promotion of nationalist ideals, but also for its very existence.
Keywords: Nationalism; Gamalinda, Eric -- Criticism and interpretation; Sociology